Synthesis and Characterization of HDTMA-Br Modified TiO₂/ZnO/CuO Photocatalyst Composite for Photodegradation of Textile Dye (Methyl Orange) - Siti Fatika; Komar Sutriah; Mohammad Khotib (Jurnal Kimia Sains dan Aplikasi, 2025)
Methyl orange exhibits low biodegradability and is difficult to remove from aqueous solutions. Photodegradation using photocatalysts offers an efficient and practical alternative for treating methyl orange dye waste. Among various semiconductor materials, TiO₂ and ZnO have attracted considerable attention due to their strong photocatalytic activity. However, excessive use of TiO₂ can lead to turbidity in the solution, reducing light penetration and consequently diminishing the efficiency of the photoreduction and photooxidation processes. Numerous studies have been conducted to control the structure, morphology, and porosity of TiO₂ to enhance its photocatalytic performance. One effective approach involves the incorporation of surfactants into composites, which can modify the optical properties, structure, and morphology of the material, thereby improving its ability to degrade methyl orange. In this study, the composite was synthesized using the precipitation method. The highest degradation efficiency of 44% was achieved at 50 minutes for a methyl orange concentration of 30 mg/L, with a composite ratio of 1:1:0.3 and an HDTMA-Br concentration of 2 CMC. The addition of HDTMA-Br enhanced the photocatalytic performance by reducing electron–hole recombination, resulting in a band gap energy of 2.87 eV within the visible light range (1.77–3.1 eV).